Model of coping strategies, resilience, psychological well-being, and perceived health among military personnel - Kuan-Jung Chen; Chia-Chen Yang; Hui-Hsun Chiang (Journal of Medical Sciences, 2018)
Background: Military personnel are confronted with physiological and psychological changes caused by stress and exposure to trauma. Although resilience may be protective against psychopathology, very few studies have explored the relationships between the resilience and coping strategies. The study aims to assess how different coping strategies affect resilience, psychological well-being (PWB), and perceived health among military personnel.Subjects and Methods: This study was a cross-sectional survey. Nuclear, biological, and chemical (NBC) soldiers and nurses in the military medical center were recruited in Taiwan in November 2015. The survey comprised the Brief COPE Scale, Ryff's PWB Scale, and the Resilience Scale for Adults, which examined the relationships among coping strategies, PWB, resilience, and perceived health. Path analysis was applied.Results: We recruited 200 participants (145 male and 177 single) aged 24.6 ± 4.7 years (range, 18–46 years). Resilience (coefficient = 0.60, P < 0.001) and PWB (coefficient = 0.33, P < 0.001) were better when using more approach-oriented coping strategies and fewer avoidant coping strategies, whereas the opposite pattern was seen when using avoidant coping (coefficient = −0.31, P < 0.001 for resilience and coefficient = −.20, P < 0.1 for PWB). PWB significantly predicted perceived health (coefficient = 0.45, P < 0.001).Conclusions: Resilience is higher when positive approach-oriented coping strategies are used, which directly affects PWB, and in turn, predicts better-perceived health. Our conceptual model indicates that interventions designed to promote approach-oriented coping strategies may help military personnel develop improved resilience, PWB, and perceived health status.